Pengaruh Current Ratio Dan Return on Assets terhadap Harga Saham pada Perusahaan Industri Farmasi yang Terdaftar dalam Bei Periode 2020-2024 - Muhammad Sukron; Putri Jasmine Rofik; Saur Costanius Simamora (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: This study aims to analyze the influence of the Current Ratio (CR) and Return on Assets (ROA) on stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. CR is employed as a liquidity indicator, while ROA reflects the efficiency of a company's asset management in generating profits. A quantitative approach was utilized, with secondary data from the financial statements of eight pharmaceutical companies selected through purposive sampling. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests to ensure model validity. The findings reveal that CR and ROA jointly have a significant effect on stock prices. Partially, CR exhibits a negative and significant impact, whereas ROA shows a positive and significant influence. With a determination coefficient of 37.3%, the study indicates that CR and ROA explain a small portion of stock price variations, while external factors contribute significantly. These findings underscore the importance of emphasizing asset management efficiency alongside liquidity in investment decision-making.